Knowledge Sharing Behavior, Disiplin Kerja dan Produktivitas Kerja Karyawan pada PT. Astria Mandiri Kadungora - Acep Abdul Basit; Intan Tenisia Prawita Sari; Ahmad Wahyu (Jurnal Wacana Ekonomi, 2019)
This research aims tp determine the influence of knowledge sharing behavior and work discipline on employee work productivity in the PT. Astria Mandiri Kadungora.Data used in this study is primary data in the form of questionnaires distributed to 57 respondents who are random sample to the Production Department of PT. Astria Mandiri Kadungora. Independent variables used in this study are Knowledge Sharing Behavior and Work Discipline, while the dependent variable in this study is Employee Work Productivity. Data analysis technique used in this study is descriptive analysis with the SPSS For Windows 16.0 program. Hypothesis testing using Multiple Linear Regression. The results showed that: (1) Knowledge Sharing Behavior variables affect Employee Work Productivity. (2) Work Discipline Variables affect Employee Work Productivity. (3) Variable Knowledge Sharing Behavior and Work Discipline affect Employee Work Productivity.